2023
DOI: 10.3390/en16073272
|View full text |Cite
|
Sign up to set email alerts
|

Thermoacoustic Combustion Stability Analysis of a Bluff Body-Stabilized Burner Fueled by Methane–Air and Hydrogen–Air Mixtures

Abstract: Hydrogen can play a key role in the gradual transition towards a full decarbonization of the combustion sector, e.g., in power generation. Despite the advantages related to the use of this carbon-free fuel, there are still several challenging technical issues that must be addressed such as the thermoacoustic instability triggered by hydrogen. Given that burners are usually designed to work with methane or other fossil fuels, it is important to investigate their thermoacoustic behavior when fueled by hydrogen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The results showed that under stable conditions, both the flame height and the inner/outer recirculation zone decreased with an increase in the hydrogen ratio, and the flame tended to attach to the bluff body more strongly. A preliminary analysis [15] of a labscale stabilized burner fuelled with a hydrogen-air mixture was conducted. CFD simulation was carried out to predict the thermodynamic properties and flame characteristics (i.e., time delay and heat release rate) of the mixtures in the hot regions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that under stable conditions, both the flame height and the inner/outer recirculation zone decreased with an increase in the hydrogen ratio, and the flame tended to attach to the bluff body more strongly. A preliminary analysis [15] of a labscale stabilized burner fuelled with a hydrogen-air mixture was conducted. CFD simulation was carried out to predict the thermodynamic properties and flame characteristics (i.e., time delay and heat release rate) of the mixtures in the hot regions.…”
Section: Introductionmentioning
confidence: 99%